Изучение биологических и основных хозяйственно-ценных признаков коллекционных сортообразцов хлопчатника вида G. barbadense L. - Мамедова, А.Д.; Алиев, Р.Т.; Мамедова, З.Б.; Исламова, Ф.М. (Фактори експериментальної еволюції організмів, 2016)
Aim. The resistance to drought and major agriculturally valuable traits of collection varietal accessions of cotton belonging to species of G. barbadense L. were studied. Methods. Physiological evaluation of stress resistance of cotton accessions to drought has been carried out according to the stress-depression of germination of seeds in a solution of sucrose. Results. The reaction of various accessions to stress enabled us to divide roughly the cotton accessions within each species into groups with different degrees of resistance: resistant, moderate resistant, low resistant and susceptible. Genotypes of cotton, characterized with complete absence of stress depression of physiological parameter, were considered as droughtresistant. Conclusions. Positive correlation observed between resistance of plants to drought and flowering date, emerging of plantlets and duration of vegetation, and there was also significant correlation between resistance to drought and duration of vegetation, between flowering date and duration of vegetation, quantity of cotton bolls and weight of cotton wool, between weights of cotton wool and weight of cotton bolls. Keywords: cotton, resistance, stress, drought, physiological parameters, productivity.